Electricity market interconnections and electricity price volatility - Fonseca, Nuno (2010)
In this paper, we present a model of changes in electricity price returns in the context of interconnected electricity markets. This model predicts an inverse relationship between the increase in interconnection capacity and the volatility of price returns in the corresponding electricity markets. This means that an increase of interconnection between two markets leads to a decrease in the volatility of their prices. We support our model with empirical results from the Australian, European and USA electricity markets. The results suggest that this inverse relationship between interconnection and volatility exists, meaning that when markets tend to be physically interconnected, variance tends to be reduced.